"R.A. Kartini" (1982) and "Kartini" (2017); Anguish and silent struggles in the narratives of Indonesian women’s empowerment role model - Pratidina, Indah S.; Pasaribu, Rouli Esther (Wacana, Journal of the Humanities of Indonesia, 2023)
This study compares the portrayal of R.A. Kartini, an Indonesian female national heroine, in the biopics Sjumandjaya’s R.A. Kartini (1982) and Bramantyo’s Kartini (2017). The films were produced in the New Order and post-Reformation eras respectively, with social and cultural values translating into context-shaped standpoints in interpreting the figure of Kartini’s. Kartini is a role model associated with empowered Indonesian women and equality in education; therefore, films produced in different social and political contexts retelling her story give insights into how these issues were framed during these eras. This study uses film discourse interpretation analysis referencing dialogues and gestures from the films to discuss power relations between male-female characters, the issue of silence and women’s voice, and sisterhood. The study finds that, although both films reconfirm the already imprinted patriarchal society’s images of Kartini in particular and women in general, there are collective efforts to rethink and question the status quo.